A natural aldehyde-functionalized whole-biomass aerogel and a method of making the same
Patent Information
- Application Number
- CN202411082357.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-08-08
AI Technical Summary
然而,PAEs与聚合物基质之间通过非共价键结合,容易向环境迁移,造成了环境污染
[0044]1、本发明采用天然交联剂首次制备了壳聚糖-淀粉样纤维共价网络气凝胶,具备优异的力学性质、结构稳定性以及高安全性。
Smart Images

Figure CN119034627B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aerogels and relates to a natural aldehyde functionalized whole biomass aerogel and its preparation method. Background Technology
[0002] Plasticizers are processing aids widely used in polymer materials to improve their processability and plasticity. Phthalate esters (PAEs) are one of the most commonly used plasticizers (>85%), with a global annual production of 4.9 million tons. However, PAEs are non-covalently bonded to the polymer matrix, making them prone to migration into the environment and causing pollution. Numerous studies have shown that PAEs pose many health risks to humans. Furthermore, PAEs can enter food through various pathways, such as contamination of food raw materials due to environmental pollution, contamination during food processing and in food-grade plastic packaging, and illegal addition. Therefore, PAEs are receiving increasing research attention worldwide. Previous studies have primarily focused on the toxicity and detection of PAEs, while the development of efficient PAE removal technologies has become a research hotspot in recent years.
[0003] Adsorption, advanced oxidation processes, and biological treatment are effective technologies for removing PAEs. Among various treatment methods, adsorption is superior to others due to its clean operation. Furthermore, the industrial-scale implementation of adsorption processes does not require large-scale plants. Therefore, non-destructive technologies such as adsorption are more attractive from both environmental protection and economic perspectives compared to advanced oxidation processes and biological treatment.
[0004] Aerogels are a class of three-dimensional materials. Their open, porous, air-filled structure gives them characteristics such as low density, high porosity, and large specific surface area, making them ideal for use as adsorbents. Considering economic factors and safety concerns, biopolymer composite aerogels (polysaccharides and proteins) have become ideal candidates for water purification, mainly due to their non-toxicity, low cost, abundant reserves, wide availability, biodegradability, and unique properties such as biocompatibility and usability. Summary of the Invention
[0005] Technical issues
[0006] Phthalate esters pose numerous health risks, but due to their wide range of applications, they can enter food processing through various routes, causing immeasurable harm. Adsorption is an excellent solution due to its convenience and high efficiency; therefore, there is a need to develop adsorbent materials suitable for removing phthalate esters.
[0007] Technical solution
[0008] This invention selects chitosan and whey protein isolate amyloid fibers as adsorbent materials, and produces an aerogel with excellent mechanical properties, structural stability and high affinity for PAEs through a simple and safe preparation process.
[0009] This invention also employs the natural biocrosslinking agent genipin to prepare a chitosan-whey protein isolate amyloid fiber covalent network to improve the mechanical properties and structural stability of the aerogel while ensuring its safety. Furthermore, natural aldehydes are grafted via Schiff base covalent interactions to enhance the mechanical properties of the chitosan-whey protein isolate amyloid fiber composite aerogel and its affinity for PAEs. To obtain satisfactory removal efficiency, the effects of two aromatic aldehydes and three aliphatic aldehydes with different chain lengths or saturations on improving PAE removal efficiency were investigated.
[0010] This invention provides a method for preparing natural aldehyde-functionalized whole biomass aerogel, comprising the following steps:
[0011] (1) Disperse chitosan in a starch fiber solution and stir to obtain a uniform mixed solution;
[0012] (2) Add genipin as a crosslinking agent to the mixed solution obtained in step (1), heat and stir for a period of time to obtain an aerogel precursor solution, let it stand for crosslinking to obtain a hydrogel;
[0013] (3) The hydrogel obtained in step (2) is frozen and then freeze-dried to obtain an aerogel;
[0014] (4) The aerogel obtained in step (3) is soaked in a natural aldehyde solution for grafting modification, then taken out and rinsed, and then dried to obtain aldehyde-functionalized aerogel.
[0015] In one embodiment of the present invention, the method for preparing the amyloid cellulose solution in step (1) includes the following steps:
[0016] S1. Purification of whey protein isolate: Add protein powder to water and stir to obtain protein dispersion. Then adjust the pH of the protein dispersion to 4-5, centrifuge to obtain supernatant, and then pass the supernatant through a 0.4-0.5μm aqueous filter membrane. Finally, freeze-dry the filtrate to obtain purified protein.
[0017] S2. Preparation of amyloid cellulose solution: Disperse the purified protein powder in water and stir to obtain a protein solution. Then adjust the pH of the protein solution to 2-2.5 and stir to obtain a whey-separated protein amyloid cellulose solution.
[0018] Furthermore, in step S1, the protein powder is one of soy protein isolate, whey protein isolate, or lysozyme.
[0019] Preferably, the protein powder in step S1 is whey protein isolate.
[0020] Furthermore, in step S1, the protein powder concentration of the protein dispersion is 5–15 wt%.
[0021] Furthermore, in step S1, the stirring is carried out at a speed of 100-1000 rpm for 8-12 hours.
[0022] Furthermore, in step S1, the centrifugation is performed at 8000–10000 × g for 20–30 minutes.
[0023] Furthermore, in step S2, the concentration of the purified protein powder is 1–5 wt%.
[0024] Furthermore, in step S2, the stirring is carried out at 70–90°C and a speed of 100–1000 rpm for 8–12 hours.
[0025] In one embodiment of the present invention, the concentration of amyloid fibers in the amyloid fiber solution in step (1) is 1-1.25% (w / v).
[0026] In one embodiment of the present invention, the amyloid cellulose solution in step (1) further contains 1-2 wt% acetic acid.
[0027] In one embodiment of the present invention, the mass ratio of chitosan to amyloid fibers in step (1) is 1.5 to 2.5:1.
[0028] In one embodiment of the present invention, in step (2), genipin is added in the form of a genipin ethanol solution; the concentration of genipin in the genipin ethanol solution is 5-15% (w / v).
[0029] In one embodiment of the present invention, the ratio of the mass of genipin added in step (2) to the mass of chitosan in step (1) is 1:15 to 25.
[0030] In one embodiment of the present invention, the heating temperature in step (2) is 45-55°C.
[0031] In one embodiment of the present invention, the heating time in step (2) is 15-30 min.
[0032] In one embodiment of the present invention, the temperature for static crosslinking in step (2) is 20-25°C.
[0033] In one embodiment of the present invention, the static crosslinking time in step (2) is 24-32h.
[0034] In one embodiment of the present invention, the freezing temperature in step (3) is -20 to -10°C and the freezing time is 15-30 hours.
[0035] In one embodiment of the present invention, the freeze-drying pressure in step (3) is 1-10 Pa, the temperature is -50 to -60 °C, and the time is 60-72 h.
[0036] In one embodiment of the present invention, the natural aldehyde in step (4) includes one or more of citral, citronellol, cinnamaldehyde, p-anisaldehyde, and trans-2-hexenal.
[0037] Preferably, the natural aldehyde in step (4) is citral.
[0038] In one embodiment of the present invention, the solvent of the natural aldehyde solution in step (4) is anhydrous ethanol; the concentration of the natural aldehyde in the natural aldehyde solution is 1.5-1.75% (w / v).
[0039] In one embodiment of the present invention, the grafting modification temperature in step (4) is 60-70°C and the time is 10-12h.
[0040] In one embodiment of the present invention, the rinsing in step (4) is performed using anhydrous ethanol.
[0041] This invention provides a natural aldehyde-functionalized whole biomass aerogel prepared according to the above method.
[0042] The application of the natural aldehyde functionalized whole biomass aerogel provided by this invention in the fields of environmental protection or food processing.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] 1. This invention uses a natural crosslinking agent to prepare a chitosan-amyloid fiber covalent network aerogel for the first time, which has excellent mechanical properties, structural stability and high safety.
[0045] 2. This invention produces an aerogel with excellent mechanical properties, structural stability, and high affinity for DBP through a simple preparation process. Furthermore, the materials used are chitosan and whey protein isolate, which are non-toxic, inexpensive, abundant, environmentally friendly, and biodegradable. Natural aldehydes are used as modifiers, possessing non-toxicity and antibacterial properties, making this invention highly valuable for industrial production.
[0046] 3. The aerogel prepared by this invention has high safety and high affinity for PAEs, and can be applied to PAE removal, especially for the food industry. Attached Figure Description
[0047] Figure 1Stress-strain curves of chitosan-amyloid fiber aerogels in Comparative Example 1 and Examples 1-5.
[0048] Figure 2 : Phthalate removal efficiency of chitosan-amyloid fiber aerogel in Comparative Example 1 and Examples 1-5.
[0049] Figure 3 : Appearance of chitosan-amyloid cellulose aerogel in Example 5.
[0050] Figure 4 Scanning electron microscope images of chitosan-amyloid fibrous aerogels in Comparative Example 1 and Example 5.
[0051] Figure 5 : Phthalate removal efficiency (a) and scanning electron microscope (b) of chitosan-amyloid fiber aerogel in Comparative Example 2 and Example 5.
[0052] Figure 6 Figure 6-10: Citral grafting amount of chitosan-amyloid fiber aerogels.
[0053] Figure 7 Stress-strain curves of chitosan-amyloid fiber aerogels in Comparative Example 1 and Examples 6-10.
[0054] Figure 8 Water contact angle diagrams of chitosan-amyloid fibrous aerogels in Comparative Example 1 and Examples 6-10.
[0055] Figure 9 Expansion rate diagrams of chitosan-amyloid fibrous aerogels in Comparative Example 1 and Examples 6-10.
[0056] Figure 10 Thermal stability diagrams of chitosan-amyloid fibrous aerogels in Comparative Example 1 and Examples 6-10.
[0057] Figure 11 : Phthalate removal efficiency of chitosan-amyloid fiber aerogel in Comparative Example 1 and Examples 6-10.
[0058] Figure 12 Example 8: Removal efficiency of various phthalates in chitosan-amyloid fiber aerogel. Detailed Implementation
[0059] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0060] In the following embodiments, the methods for preparing whey protein isolate amyloid fibers are as follows:
[0061] First, the whey protein isolate is purified. Simply put, 10g of whey protein isolate powder is added to 100mL of deionized water. Then, the mixture is stirred overnight at 600rpm using a magnetic stirrer to ensure complete protein hydration. The resulting protein dispersion is then adjusted to pH 4.75 and centrifuged at 10000×g for 30 minutes to remove any insoluble substances. The supernatant is then passed through a 0.45μm aqueous filter membrane to remove any remaining insoluble protein. Finally, the purified whey protein isolate is obtained by vacuum freeze-drying.
[0062] For the preparation of amyloid fibers, 2g of purified whey protein isolate powder was dispersed in 100mL of deionized water and stirred overnight to ensure full hydration of the protein. The pH of the resulting protein solution was adjusted to 2.0, and then stirred at 300rpm for 8 hours in a 90℃ water bath to promote protein fiber formation. Finally, the solution was cooled in an ice-water bath for at least 30 minutes to terminate the fibrillation reaction, yielding a whey protein isolate amyloid fiber solution (2%, w / v).
[0063] Example 1
[0064] Step 1: Disperse 0.8g of chitosan in 40mL of 1% (w / v) whey protein isolate amyloid cellulose solution (containing 1% acetic acid), and stir until completely dissolved to obtain a homogeneous mixed solution.
[0065] Step 2: Add 0.4 mL of genipin ethanol solution (10% (w / v)) as a crosslinking agent to the mixed solution obtained in Step 1, stir at 50℃ and 300 rpm for 20 min to obtain a uniform aerogel precursor solution, and let it stand at room temperature for 24 h to promote crosslinking and obtain hydrogel.
[0066] Step 3: Freeze the hydrogel obtained in Step 2 in a -18℃ freezer for 24 hours, and then freeze-dry it under vacuum for 60 hours to obtain an aerogel.
[0067] Step 4: Immerse the aerogel obtained in Step 3 in a 1.5% (w / v) cinnamaldehyde ethanol solution and keep it at 65℃ for 10 h for grafting modification. Then take it out and rinse it thoroughly with anhydrous ethanol, and dry it in a fume hood for 24 h to obtain cinnamaldehyde-functionalized chitosan-whey protein isolate amyloid fiber aerogel.
[0068] Example 2
[0069] Step 1: Disperse 0.8g of chitosan in 40mL of 1% (w / v) whey protein isolate amyloid cellulose solution (containing 1% acetic acid), and stir until completely dissolved to obtain a homogeneous mixed solution.
[0070] Step 2: Add 0.4 mL of genipin ethanol solution (10% (w / v)) as a crosslinking agent to the mixed solution obtained in Step 1, stir at 50℃ and 300 rpm for 20 min to obtain a uniform aerogel precursor solution, and let it stand at room temperature for 24 h to promote crosslinking and obtain hydrogel.
[0071] Step 3: Freeze the hydrogel obtained in Step 2 in a -18℃ freezer for 24 hours, and then freeze-dry it under vacuum for 60 hours to obtain an aerogel.
[0072] Step 4: Immerse the aerogel obtained in Step 3 in a 1.5% (w / v) p-anisaldehyde ethanol solution and incubate at 65°C for 10 h for graft modification. Then remove it, rinse thoroughly with anhydrous ethanol, and dry in a fume hood for 24 h to obtain p-anisaldehyde functionalized chitosan-whey protein isolate amyloid fiber aerogel.
[0073] Example 3
[0074] Step 1: Disperse 0.8g of chitosan in 40mL of 1% (w / v) whey protein isolate amyloid cellulose solution (containing 1% acetic acid), and stir until completely dissolved to obtain a homogeneous mixed solution.
[0075] Step 2: Add 0.4 mL of genipin ethanol solution (10% (w / v)) as a crosslinking agent to the mixed solution obtained in Step 1, stir at 50℃ and 300 rpm for 20 min to obtain a uniform aerogel precursor solution, and let it stand at room temperature for 24 h to promote crosslinking and obtain hydrogel.
[0076] Step 3: Freeze the hydrogel obtained in Step 2 in a -18℃ freezer for 24 hours, and then freeze-dry it under vacuum for 60 hours to obtain an aerogel.
[0077] Step 4: Immerse the aerogel obtained in Step 3 in a 1.5% (w / v) trans-2-hexenal ethanol solution and incubate at 65°C for 10 h for graft modification. Then remove it, rinse thoroughly with anhydrous ethanol, and dry in a fume hood for 24 h to obtain trans-2-hexenal functionalized chitosan-whey protein isolate amyloid fiber aerogel.
[0078] Example 4
[0079] Step 1: Disperse 0.8g of chitosan in 40mL of 1% (w / v) whey protein isolate amyloid cellulose solution (containing 1% acetic acid), and stir until completely dissolved to obtain a homogeneous mixed solution.
[0080] Step 2: Add 0.4 mL of genipin ethanol solution (10% (w / v)) as a crosslinking agent to the mixed solution obtained in Step 1, stir at 50℃ and 300 rpm for 20 min to obtain a uniform aerogel precursor solution, and let it stand at room temperature for 24 h to promote crosslinking and obtain hydrogel.
[0081] Step 3: Freeze the hydrogel obtained in Step 2 in a -18℃ freezer for 24 hours, and then freeze-dry it under vacuum for 60 hours to obtain an aerogel.
[0082] Step 4: Immerse the aerogel obtained in Step 3 in a 1.5% (w / v) citronellal ethanol solution and keep it at 65℃ for 10 h for grafting modification. Then take it out and rinse it thoroughly with anhydrous ethanol, and dry it in a fume hood for 24 h to obtain citronellal functionalized chitosan-whey protein isolate amyloid fiber aerogel.
[0083] Example 5
[0084] Step 1: Disperse 0.8g of chitosan in 40mL of 1% (w / v) whey protein isolate amyloid cellulose solution (containing 1% acetic acid), and stir until completely dissolved to obtain a homogeneous mixed solution.
[0085] Step 2: Add 0.4 mL of genipin ethanol solution (10% (w / v)) as a crosslinking agent to the mixed solution obtained in Step 1, stir at 50℃ and 300 rpm for 20 min to obtain a uniform aerogel precursor solution, and let it stand at room temperature for 24 h to promote crosslinking and obtain hydrogel.
[0086] Step 3: Freeze the hydrogel obtained in Step 2 in a -18℃ freezer for 24 hours, and then freeze-dry it under vacuum for 60 hours to obtain an aerogel.
[0087] Step 4: Immerse the aerogel obtained in Step 3 in a 1.5% (w / v) citral ethanol solution and keep it at 65℃ for 10 h for grafting modification. Then take it out and rinse it thoroughly with anhydrous ethanol, and dry it in a fume hood for 24 h to obtain citral-functionalized chitosan-whey protein isolate amyloid fiber aerogel.
[0088] Comparative Example 1
[0089] Step 1: Disperse 0.8g of chitosan in 40mL of 1% (w / v) whey protein isolate amyloid cellulose solution (containing 1% acetic acid), and stir until completely dissolved to obtain a homogeneous mixed solution.
[0090] Step 2: Add 0.4 mL of genipin ethanol solution (10% (w / v)) as a crosslinking agent to the mixed solution obtained in Step 1, stir at 50℃ and 300 rpm for 20 min to obtain a uniform aerogel precursor solution, and let it stand at room temperature for 24 h to promote crosslinking and obtain hydrogel.
[0091] Step 3: Freeze the hydrogel obtained in Step 2 in a -18℃ freezer for 24 hours, and then freeze-dry it under vacuum for 60 hours to obtain an aerogel without grafting with natural aldehydes.
[0092] Comparative Example 2
[0093] Step 1: Disperse 1.2g of chitosan in 40mL of deionized water (containing 1% acetic acid) and stir until completely dissolved to obtain a homogeneous mixed solution.
[0094] Step 2: Add 0.4 mL of genipin ethanol solution (10% (w / v)) as a crosslinking agent to the mixed solution obtained in Step 1, stir at 50℃ and 300 rpm for 20 min to obtain a uniform aerogel precursor solution, and let it stand at room temperature for 24 h to promote crosslinking and obtain hydrogel.
[0095] Step 3: Freeze the hydrogel obtained in Step 2 in a -18℃ freezer for 24 hours, and then freeze-dry it under vacuum for 60 hours to obtain an aerogel.
[0096] Step 4: Immerse the aerogel obtained in Step 3 in a 1.5% (w / v) citral ethanol solution and keep it at 65℃ for 10 h for grafting modification. Then take it out and rinse it thoroughly with anhydrous ethanol, and dry it in a fume hood for 24 h to obtain aldehyde-functionalized chitosan aerogel.
[0097] Testing process:
[0098] 0.8 g of aerogel samples from Comparative Example 1 and Examples 1-5 were placed in 100 mL of DBP solution (2 mg / L), and then placed on a shaker at 120 rpm at 25 °C until adsorption equilibrium was reached. The aerogels were then removed, and the residual concentration of DBP was determined by gas chromatography-mass spectrometry.
[0099] Test results:
[0100] Figure 1 The stress-strain curves of chitosan-amyloid fiber aerogels in Comparative Example 1 and Examples 1-5 are shown. It can be seen that all aerogels exhibit good mechanical properties. The maximum compressive strength of the unmodified aerogel in Comparative Example 1 still reaches 595 kPa, which is attributed to its covalent gel network. The mechanical properties of the aerogels in Examples 1-5 are further improved after aldehyde modification, exhibiting higher stress at the same strain, indicating enhanced mechanical strength. Among them, the aerogel in Example 5 exhibits the best mechanical properties, indicating that citral grafting is an effective strategy for improving chitosan-amyloid fiber aerogels, possibly due to its good compatibility with the material matrix.
[0101] Figure 2 The DBP removal efficiencies of chitosan-amyloid cellulose aerogels in Comparative Example 1 and Examples 1-5 are shown. It can be seen that the chitosan-amyloid cellulose aerogel in Comparative Example 1 exhibits the lowest DBP removal efficiency, possibly due to its low DBP affinity. The aerogels in Examples 1-5, after grafting with natural aldehydes, show significantly improved DBP removal efficiency, mainly attributed to the hydrophobic interactions and π-π stacking between the natural aldehyde molecules and DBP. Furthermore, compared to Examples 1-2, the aerogels in Examples 3-5 demonstrate higher DBP removal capabilities, indicating that the strong hydrophobic interactions between orthoaldehydes and DBP are key to the high removal efficiency, rather than the π-π stacking of aromatic aldehydes. The increasing trend in removal efficiency of the aerogels in Examples 3-5 suggests that increased orthoaldehyde chain length and unsaturation may also promote DBP adsorption.
[0102] Figure 3 The image shows the appearance of the chitosan-amyloid cellulose aerogel in Example 5. It can be seen that the prepared aerogel can stand stably on dandelion without damaging its structure, indicating that it has the characteristics of low density and high porosity, and is suitable for adsorption applications.
[0103] Figure 4Scanning electron microscopy (SEM) images of the chitosan-amyloid fibrous aerogels in Comparative Example 1 and Example 5 are shown. It can be seen that the aerogel of Comparative Example 1 has randomly distributed irregular macropores and a honeycomb-like macroporous structure, which is due to the large ice crystals formed during freezing at -18°C. The porous structure provides abundant active sites for the adsorption of pollutant molecules. The aerogel of Example 5, after grafting with citral, maintained its original honeycomb-like macroporous structure, indicating good structural stability and resistance to environmental drying during the modification process. Furthermore, compared to the aerogel of Comparative Example 1, the aerogel network structure of Example 5 is denser, which is beneficial for adsorption applications. More importantly, the pore walls of the aerogel of Example 5 are thicker than those of Comparative Example 1, indicating that the grafting of citral increases the pore wall thickness, which can improve the mechanical properties and stability of the aerogel by creating a more robust porous structure.
[0104] Figure 5 The DBP removal efficiency (a) and scanning electron microscopy (b) of the chitosan-amyloid fibrous aerogels in Comparative Example 2 and Example 5 are shown. Figure 5 As can be seen, compared with Example 5, the chitosan aerogel in Comparative Example 2 has a lower removal efficiency, indicating the positive role of amyloid fibers in DBP removal. Figure 5 b. It can be seen that the aerogel of Comparative Example 2 has a similar pore structure to the aerogel of Example 5. However, its pore wall surface is smooth and there is no fibrous material attached, indicating that the amyloid fibers are attached to the aerogel surface. Improving the roughness and providing a large number of adsorption sites are the key to improving the removal efficiency.
[0105] Example 6
[0106] Step 1: Disperse 0.8g of chitosan in 40mL of 1% (w / v) whey protein isolate amyloid cellulose solution (containing 1% acetic acid), and stir until completely dissolved to obtain a homogeneous mixed solution.
[0107] Step 2: Add 0.4 mL of genipin ethanol solution (10% (w / v)) as a crosslinking agent to the mixed solution obtained in Step 1, stir at 50℃ and 300 rpm for 20 min to obtain a uniform aerogel precursor solution, and let it stand at room temperature for 24 h to promote crosslinking and obtain hydrogel.
[0108] Step 3: Freeze the hydrogel obtained in Step 2 in a -18℃ freezer for 24 hours, and then freeze-dry it under vacuum for 60 hours to obtain an aerogel.
[0109] Step 4: Immerse the aerogel obtained in Step 3 in a 0.5% (w / v) citral ethanol solution and keep it at 65℃ for 10 h for grafting modification. Then take it out and rinse it thoroughly with anhydrous ethanol, and dry it in a fume hood for 24 h to obtain citral-functionalized chitosan-whey protein isolate amyloid fiber aerogel.
[0110] Example 7
[0111] Step 1: Disperse 0.8g of chitosan in 40mL of 1% (w / v) whey protein isolate amyloid cellulose solution (containing 1% acetic acid), and stir until completely dissolved to obtain a homogeneous mixed solution.
[0112] Step 2: Add 0.4 mL of genipin ethanol solution (10% (w / v)) as a crosslinking agent to the mixed solution obtained in Step 1, stir at 50℃ and 300 rpm for 20 min to obtain a uniform aerogel precursor solution, and let it stand at room temperature for 24 h to promote crosslinking and obtain hydrogel.
[0113] Step 3: Freeze the hydrogel obtained in Step 2 in a -18℃ freezer for 24 hours, and then freeze-dry it under vacuum for 60 hours to obtain an aerogel.
[0114] Step 4: Immerse the aerogel obtained in Step 3 in a 1.0% (w / v) citral ethanol solution and keep it at 65℃ for 10 h for grafting modification. Then take it out and rinse it thoroughly with anhydrous ethanol, and dry it in a fume hood for 24 h to obtain citral-functionalized chitosan-whey protein isolate amyloid fiber aerogel.
[0115] Example 8
[0116] Step 1: Disperse 0.8g of chitosan in 40mL of 1% (w / v) whey protein isolate amyloid cellulose solution (containing 1% acetic acid), and stir until completely dissolved to obtain a homogeneous mixed solution.
[0117] Step 2: Add 0.4 mL of genipin ethanol solution (10% (w / v)) as a crosslinking agent to the mixed solution obtained in Step 1, stir at 50℃ and 300 rpm for 20 min to obtain a uniform aerogel precursor solution, and let it stand at room temperature for 24 h to promote crosslinking and obtain hydrogel.
[0118] Step 3: Freeze the hydrogel obtained in Step 2 in a -18℃ freezer for 24 hours, and then freeze-dry it under vacuum for 60 hours to obtain an aerogel.
[0119] Step 4: Immerse the aerogel obtained in Step 3 in a 1.5% (w / v) citral ethanol solution and keep it at 65℃ for 10 h for grafting modification. Then take it out and rinse it thoroughly with anhydrous ethanol, and dry it in a fume hood for 24 h to obtain citral-functionalized chitosan-whey protein isolate amyloid fiber aerogel.
[0120] Example 9
[0121] Step 1: Disperse 0.8g of chitosan in 40mL of 1% (w / v) whey protein isolate amyloid cellulose solution (containing 1% acetic acid), and stir until completely dissolved to obtain a homogeneous mixed solution.
[0122] Step 2: Add 0.4 mL of genipin ethanol solution (10% (w / v)) as a crosslinking agent to the mixed solution obtained in Step 1, stir at 50℃ and 300 rpm for 20 min to obtain a uniform aerogel precursor solution, and let it stand at room temperature for 24 h to promote crosslinking and obtain hydrogel.
[0123] Step 3: Freeze the hydrogel obtained in Step 2 in a -18℃ freezer for 24 hours, and then freeze-dry it under vacuum for 60 hours to obtain an aerogel.
[0124] Step 4: Immerse the aerogel obtained in Step 3 in a 2.0% (w / v) citral ethanol solution and keep it at 65℃ for 10 h for grafting modification. Then take it out and rinse it thoroughly with anhydrous ethanol, and dry it in a fume hood for 24 h to obtain citral-functionalized chitosan-whey protein isolate amyloid fiber aerogel.
[0125] Example 10
[0126] Step 1: Disperse 0.8g of chitosan in 40mL of 1% (w / v) whey protein isolate amyloid cellulose solution (containing 1% acetic acid), and stir until completely dissolved to obtain a homogeneous mixed solution.
[0127] Step 2: Add 0.4 mL of genipin ethanol solution (10% (w / v)) as a crosslinking agent to the mixed solution obtained in Step 1, stir at 50℃ and 300 rpm for 20 min to obtain a uniform aerogel precursor solution, and let it stand at room temperature for 24 h to promote crosslinking and obtain hydrogel.
[0128] Step 3: Freeze the hydrogel obtained in Step 2 in a -18℃ freezer for 24 hours, and then freeze-dry it under vacuum for 60 hours to obtain an aerogel.
[0129] Step 4: Immerse the aerogel obtained in Step 3 in a 3.0% (w / v) citral ethanol solution and keep it at 65℃ for 10 h for grafting modification. Then take it out and rinse it thoroughly with anhydrous ethanol, and dry it in a fume hood for 24 h to obtain citral-functionalized chitosan-whey protein isolate amyloid fiber aerogel.
[0130] Testing process:
[0131] 0.8 g of aerogel samples from Comparative Example 1 and Examples 6-10 were placed in 100 mL of PAEs solution (2 mg / L), and then placed on a shaker at 120 rpm at 25 °C until adsorption equilibrium was reached. The aerogels were then removed, and the residual concentration of PAEs was determined by gas chromatography-mass spectrometry.
[0132] Test results:
[0133] Figure 6 The citral grafting amount of chitosan-amyloid fiber aerogels in Examples 6-10 is shown. It can be seen that the citral grafting amount increases linearly with the increase of citral concentration, reaching a maximum of 0.31 g / g, indicating that the surface of chitosan-amyloid fiber aerogels contains a large number of active amino groups as citral grafting sites.
[0134] Figure 7 The stress-strain curves of chitosan-amyloid fibrous aerogels in Comparative Example 1 and Examples 6-10 are shown. It can be seen that all aerogels exhibit good mechanical properties, which may be related to their honeycomb pore wall structure. The chitosan-amyloid fibrous aerogel in Comparative Example 1 has the lowest compressive strength. With increasing citral concentration, the compressive stress of the aerogel gradually increases. The maximum compressive strength of the aerogel increases from 595 kPa in Comparative Example 1 to 1005 kPa in Example 10, an increase of 68.9%. This confirms that citral grafting can further improve the mechanical properties of chitosan-amyloid fibrous aerogels. The increase in density and cell wall thickness of the chitosan-amyloid fibrous aerogels caused by citral grafting are likely the main contributors to this effect. Notably, when the citral concentration exceeds 2% (w / v), the compressive stress of the aerogel does not increase significantly, indicating the limited ability of citral to improve the mechanical properties of the material.
[0135] Figure 8 The water contact angles (WCA) of chitosan-amyloid fibrous aerogels in Comparative Example 1 and Examples 6-10 are shown. It can be seen that the water contact angle of the chitosan-amyloid fibrous aerogel in Comparative Example 1 is 0°, mainly due to the presence of numerous hydrophilic groups in its network. After citral grafting, the water contact angle of the aerogel significantly increased (67.0-121.9°), possibly due to the anchoring of low-polarity groups (alkane chains) on the surface of the chitosan-amyloid fibrous aerogel and the consumption of hydrophilic amino groups, indicating successful citral grafting. When the citral concentration is below 1.5%, the water contact angle of the chitosan-amyloid fibrous aerogels in Examples 6-7 does not exceed 90°, still exhibiting hydrophilicity. This may be attributed to the lower citral grafting density, where the original hydrophilic groups still dominate. With further increases in citral concentration, the WCA of the aerogel in Example 5 reaches 121.9°, indicating a higher citral grafting density.
[0136] Figure 9 The swelling rates of chitosan-amyloid fibrous aerogels in Comparative Example 1 and Examples 6-10 are shown. It can be seen that the chitosan-amyloid fibrous aerogel in Comparative Example 1 has the highest water swelling rate of 26.42 g / g. This is attributed to the fact that the numerous hydrophilic groups in the aerogel retain water molecules within its network structure through hydrogen bonding. Despite this, the volume of the aerogel did not change significantly before and after water absorption, and the structure remained stable. After citral grafting, the swelling rate of the chitosan-amyloid fibers in Examples 6-10 was significantly reduced, with the aerogel in Example 10 showing a swelling rate as low as 7.81 g / g, less than 30% of that of the aerogel in Comparative Example 1, indicating good structural stability in water. This change became more significant with increasing citral grafting rate. This may be attributed to the low-polarity alkane chains hindering the diffusion of water into the aerogel interior. Another possible reason is that citral grafting may have increased the rigidity of the aerogel, limiting the deformability of the polymer network and thus reducing the water swelling rate.
[0137] Figure 10 The thermal stability of chitosan-amyloid cellulose aerogels in Comparative Example 1 and Examples 6-10 is shown. It can be seen that the weight loss process of the chitosan-amyloid cellulose aerogel in Comparative Example 1 mainly consists of three steps. The first step occurs in the temperature range of 30-218°C, with a weight loss of 22.09%, which is related to the strong hydrophilicity of the aerogel in Comparative Example 1. The first step can be divided into two stages: the first stage (30-120°C) is attributed to the loss of free water and water linked by hydrogen bonds in the sample; the second stage is attributed to the release of water that is more tightly linked by polar interactions with carboxylic acid groups. The second step occurs in the temperature range of 218-300°C, with a weight loss of 22.51%, which may be attributed to the depolymerization of the polymer network structure, hydroxyl group decomposition, and deacetylation of chitosan. A subsequent weight loss of 29.41% occurs between 300-500°C, corresponding to the carbonization of proteins and polysaccharides. Compared to the aerogel of Comparative Example 1, the aerogels of Examples 6-10 exhibited moisture losses of 8.73-11.87% between 30-120°C, depending on the citral concentration, which was significantly lower than the moisture loss of the aerogel sample in Comparative Example 1. This may be related to the excellent hydrophobic properties of the aldehyde-functionalized chitosan-amyloid fibrous aerogel, with hydrophobicity increasing with increasing citral concentration, leading to a reduction in residual moisture on the aerogel surface and inside. This is consistent with the contact angle analysis results. Figure 10 b. It can be observed that the initial decomposition temperature of the aerogels in Examples 6-10 is approximately 185°C, lower than that of Comparative Example 1 (218°C), indicating that citral grafting leads to a slight decrease in the thermal stability of the aerogels. Nevertheless, the aerogel samples of Examples 6-10 remain stable at temperatures up to nearly 200°C.
[0138] Figure 11The removal efficiencies of chitosan-amyloid cellulose aerogels in Comparative Example 1 and Examples 6-10 for dibutyl phthalate (PAE) are shown. It can be seen that the aerogel of Comparative Example 1 has the lowest PAE removal efficiency, which may be attributed to its weaker hydrophobic interactions, indicating that citral grafting is an effective strategy to improve the affinity of PAEs. The aerogels of Examples 6-10 showed different removal efficiencies for PAE, with Example 8 exhibiting the highest removal efficiency, possibly attributed to its higher citral grafting amount and suitable hydrophobic properties.
[0139] Figure 12 The different PAEs removal efficiencies of the chitosan-amyloid fiber aerogel in Example 8 are shown. It can be seen that due to the abundant functional groups and numerous adsorption sites on the aerogel surface, as well as the high affinity of PAEs caused by citral grafting, the aerogel can adsorb PAEs through hydrogen bonds, π-π stacking, and hydrophobic interactions. It exhibits good removal efficiency for dibutyl phthalate, diisobutyl phthalate, dipentyl phthalate, dihexyl phthalate, dioctyl phthalate, di(2-ethylhexyl) phthalate, and butylbenzene phthalate.
[0140] The embodiments provided above are not intended to limit the scope of the invention, nor are the described steps intended to limit the order of execution. Any obvious modifications made to the invention by those skilled in the art based on existing common knowledge also fall within the scope of protection defined by the claims.
Claims
1. A method for preparing a natural aldehyde-functionalized whole biomass aerogel, characterized in that, The natural aldehyde-functionalized biomass aerogel is used for PAE removal; The preparation method includes the following steps: (1) Disperse chitosan in a starch fiber solution and stir to obtain a uniform mixed solution; (2) Add genipin as a crosslinking agent to the mixed solution obtained in step (1), heat and stir for a period of time to obtain an aerogel precursor solution, let it stand for crosslinking to obtain a hydrogel; (3) The hydrogel obtained in step (2) is frozen and then freeze-dried to obtain an aerogel; (4) The aerogel obtained in step (3) is soaked in a natural aldehyde solution for graft modification, then taken out and rinsed, and then dried to obtain a natural aldehyde functionalized whole biomass aerogel; the solvent of the natural aldehyde solution is anhydrous ethanol; the concentration of natural aldehyde in the natural aldehyde solution is 1.5-1.75%, w / v; the natural aldehyde is citral. The method for preparing the amyloid fibers includes the following steps: S1. Purification of whey protein isolate: Add protein powder to water and stir to obtain a protein dispersion. Then adjust the pH of the protein dispersion to 4-5, centrifuge to collect the supernatant, and then pass the supernatant through a 0.4-0.5μm aqueous filter membrane. Finally, freeze-dry the filtrate to obtain the purified protein; the protein powder is whey protein isolate. S2. Preparation of amyloid fibers: Disperse the purified protein powder in water, stir to obtain a protein solution, then adjust the pH of the protein solution to 2~2.5, stir, and dry to obtain whey-separated protein amyloid fibers.
2. The preparation method according to claim 1, characterized in that, In step S1, the protein powder concentration of the protein dispersion is 5-15 wt%; stirring is performed at 100-1000 rpm for 8-12 hours; and centrifugation is performed at 8000-10000 × g for 20-30 minutes.
3. The preparation method according to claim 1, characterized in that, In step S2, the concentration of the purified protein powder in the protein solution is 1-5 wt%; the stirring is carried out at 70-90°C and 100-1000 rpm for 8-12 hours.
4. The preparation method according to claim 1, characterized in that, In step (1), the concentration of amyloid fibers in the amyloid fiber solution is 1-1.25%, w / v; the amyloid fiber solution contains 1-2 wt% acetic acid.
5. The preparation method according to claim 1, characterized in that, In step (1), the mass ratio of chitosan to amyloid fibers is 1.5~2.5:
1.
6. The preparation method according to claim 1, characterized in that, In step (2), genipin is added in the form of a genipin ethanol solution; the concentration of genipin in the genipin ethanol solution is 5~15%, w / v; the ratio of the mass of genipin added to the mass of chitosan in step (1) is 1:15~25.
7. The preparation method according to claim 1, characterized in that, In step (2), the heating temperature is 45-55 ℃; the heating time is 15-30 min; the temperature for static crosslinking is 20-25 ℃; and the static crosslinking time is 24-32 h.
8. The preparation method according to claim 1, characterized in that, In step (3), the freezing temperature is -20~-10℃ and the freezing time is 15-30h.
9. The preparation method according to claim 1, characterized in that, In step (3), the freeze-drying pressure is 1-10 Pa, the temperature is -50~-60℃, and the time is 60-72h.
10. The preparation method according to claim 1, characterized in that, In step (4), the grafting modification temperature is 60-70℃ and the time is 10-12h.
11. The preparation method according to claim 1, characterized in that, In step (4), rinsing is performed using anhydrous ethanol.
Citation Information
Patent Citations
Egg preservation whey protein self-assembly fiber coating agent and application method thereof
CN103444839A
Preparation method and application of super-hydrophobic aerogel with both ultrafast oil adsorption capacity and high compression recovery performance
CN115282888A
Amyloid fiber-ferulic acid-chitosan double-network hydrogel as well as preparation method and application thereof
CN115353646A